Identification of Novel Mutations in FAH Gene and Prenatal Diagnosis of Tyrosinemia in Indian Family - Jayesh J. Sheth; Chitra M. Ankleshwaria; Rajeshwari Pawar; Frenny J. Sheth (Case Reports in Genetics)
Carrier of tyrosinemia type I was diagnosed by sequencing FAH (fumarylacetoacetate hydrolase) gene. It leads to the identification of heterozygous status for both c.648C>G (p.Ile216Met) and c.1159G>A (p.Gly387Arg) mutations in exons 8 and 13, respectively, in the parents. The experimental program PolyPhen, SIFT, and MT predicts former missense point mutation as “benign” that creates a potential donor splice site and later one as “probably damaging” which disrupts secondary structure of protein.